1349. Global Surveillance of Cefiderocol Against Gram-Negative Clinical Strains Collected in North America: SIDERO-WT-2015. (26th November 2018) - Tsuji, Masakatsu; Hackel, Meredith; Echols, Roger; Yamano, Yoshinori; Sahm, Dan
Abstract: Background: Cefiderocol (CFDC) is a novel parenteral siderophore cephalosporin with potent activity against a wide range of Gram-negative pathogens, including carbapenem-resistant strains. Additionally, a recently conducted in vivo murine-based study has demonstrated an incremental exposure-response profile over a dose range without the appearance of adaptive resistance. In this study, we evaluated the in vitro activity of CFDC and comparator agents against clinical isolates collected in 2015–2016 from North America from SIDERO-WT-2015 surveillance study. Methods: A total of 3, 602 isolates (2, 470 Enterobacteriaceae, 223 A. baumannii, 85 Acinetobacter spp., 619 P. aeruginosa, 165 S. maltophilia and 17 Burkholderia cepacia, and 23 Burkholderia spp.) collected from the United States and Canada in 2015–2016 were tested. MICs were determined for CFDC, cefepime (FEP), ceftazidime–avibactam (CZA), ceftolozane–tazobactam (C/T), ciprofloxacin (CIP), colistin (CST), and meropenem (MEM) by broth microdilution and interpreted according to CLSI guidelines. As recommended by CLSI, cefiderocol was tested in iron-depleted cation-adjusted Mueller–Hinton broth (ID-CAMHB). Carbapenem nonsusceptible (Carb-NS) strains were defined as MEM MIC ≥2 µg/mL for Enterobacteriaceae, and ≥4 µg/mL for nonfermenters. Results: CFDC exhibited potent in vitro activity against 3, 602 strains of Gram-negative bacteria with an overall MIC90 of 0.5 mg/mL. As shown in the following table, MIC90 of CFDC against P. aeruginosa, A. baumannii, S. maltophilia, and Enterobacteriaceae including the subset of Carb-NS isolates were 0.5, 2, 0.5 and 0.5 mg/mL, respectively. At 4 mg/mL, CFDC inhibited the growth of 99.6% of the isolates while 18.1%, 12.6%, and 13.8% showed resistance to CZA, C/T, and CST, respectively. Conclusion: CFDC demonstrated potent in vitro activity against the teat isolates collected from North America with greater than 99.6% of isolates having MIC values ≤4 mg/mL, including Carb-NS isolates of A. baumannii, P. aeruginosa, and Enterobacteriaceae . These findings indicate that this agent has high potential for treating infections caused by these problematic organisms. Disclosures: M. Tsuji, Shionogi & Co., Ltd.: Employee, Salary. M. Hackel, IHMA, Inc.: Employee, Salary. Y. Yamano, Shionogi & Co., Ltd.: Employee, Salary. D. Sahm, IHMA, Inc.: Employee, Salary.